Integrated Programs for Early Recognition of Severe Mental Disorders: Recommendations From an Italian Multicenter Project - Parabiaghi, Alberto; Confalonieri, Linda; Magnani, Nadia; Lora, Antonio; Butteri, Emanuela; Prato, Katia; Vaggi, Marco; Percudani, Mauro Emilio (Frontiers in Psychiatry, 2019)
The onset of mental disorders often occurs in adolescence or young adulthood, but the process of early diagnosis and access to timely effective and appropriate services can still be a challenge. The goal of this paper is to describe a pilot implementation case of the Ultra-High Risk (UHR) paradigm in six Italian departments of mental health employing an integrated approach to address clinical practice and service organization for youth in a broader preventive perspective. This approach entailed the integration of the UHR paradigm with a service provision model which prioritize prevention and the promotion of local community coalitions to improve youth service accessibility. The multicenter Italian Project “Integrated programs for recognition and early treatment of severe mental disorders in youths” funded by the National Centre for Disease Prevention and Control (CCM 2013 Project) implemented in three Italian regions will be described. As a result of syner-gic actions targeting accessibility of young individuals to innovative youth mental health teams, a total of 376 subjects aged 15–24 years were recruited by integrated youth services within twelve months. Subjects have been screened by integrated multidisciplinary mental health youth teams employing standardized procedure and evidence-based clinical assessment instruments for at risk mental states in young subjects (e.g. Comprehensive Assessment At Risk Mental States). Consi-dering the three UHR categories included in CAARMS, the percentage of UHR subjects was 35% (n=127) of the sample. In conclusion, future strategies to improve the organization of youth mental health services from a wider preventive perspective will be proposed.